AN ANALYSIS OF POSITIVE AND NEGATIVE FACE IN “THE CROODS MOVIE” - Muhamamad Ari Syaputra (VISION, 2019)
This study focuses on the management face in the conversation in the croods movie. This study was aimed at identifying a face management which is defined as any interaction word that is generally related to politeness. politeness is seen as a feature of interpersonal conduct whereby a person ‘shows regard for another person by trying to make that person feel comfortable or by making an obvious effort to avoid making that person feel uncomfortable’. Politeness is a feature of interpersonal conduct centered on the concept of face. The concept of face to a certain extent determines how a conversation can be conducted efficiently, effectively, and politely. This is descriptive and qualitative study is done under the scope of pragmatics that is implements theory of management face proposed by Goffman. It can be divide into two face; positive and negative face. The concepts of face in “the croods movie” discourse yield two concept namely positive and negative concepts. Positive face is the need to be accepted, even liked by others, to be treated as a member of the group and to know that his or her wants are shared by others. Negative face is the need to be independent to have a freedom of action and not to be imposed by others. The data obtained through movie of the croods with duration one half hour. After collecting the data, the writer identified and classified the data which are needed from the conversation specifically indicated positive and negative face. The finding of the study shows that are many conversation indicated positive and negative face, in this paper the writer only show five evident that showed to indicate positive and negative face.